The truth about Stacey - Martin, Ann M., 1955-; Telgemeier, Raina (Baby-sitters Club (Graphix (Firm)), 2015)
Joining the Baby-sitter's Club after moving to a new town, Stacey helps her new friends outmaneuver a rival sitter group while coming to terms with her diabetes.